Simplifying
5j^{2} + -20 = 0
Reorder the terms:
-20 + 5j^{2} = 0
Solving
-20 + 5j^{2} = 0
Solving for variable 'j'.
Move all terms containing j to the left, all other terms to the right.
Add '20' to each side of the equation.
-20 + 20 + 5j^{2} = 0 + 20
Combine like terms: -20 + 20 = 0
0 + 5j^{2} = 0 + 20
5j^{2} = 0 + 20
Combine like terms: 0 + 20 = 20
5j^{2} = 20
Divide each side by '5'.
j^{2} = 4
Simplifying
j^{2} = 4
Reorder the terms:
-4 + j^{2} = 4 + -4
Combine like terms: 4 + -4 = 0
-4 + j^{2} = 0
Factor a difference between two squares.
(2 + j)(-2 + j) = 0
#### Subproblem 1

Set the factor '(2 + j)' equal to zero and attempt to solve:
Simplifying
2 + j = 0
Solving
2 + j = 0
Move all terms containing j to the left, all other terms to the right.
Add '-2' to each side of the equation.
2 + -2 + j = 0 + -2
Combine like terms: 2 + -2 = 0
0 + j = 0 + -2
j = 0 + -2
Combine like terms: 0 + -2 = -2
j = -2
Simplifying
j = -2
#### Subproblem 2

Set the factor '(-2 + j)' equal to zero and attempt to solve:
Simplifying
-2 + j = 0
Solving
-2 + j = 0
Move all terms containing j to the left, all other terms to the right.
Add '2' to each side of the equation.
-2 + 2 + j = 0 + 2
Combine like terms: -2 + 2 = 0
0 + j = 0 + 2
j = 0 + 2
Combine like terms: 0 + 2 = 2
j = 2
Simplifying
j = 2#### Solution

j = {-2, 2}